A Review Article on Corona Virus 2019-nCoV (COVID-19) (International Journal of Nursing Education, 2020)
Coronaviruses are a group of viruses that cause diseases in mammals and birds. In humans, the viruses causerespiratory infections which are typically mild, including the common cold; however, rarer forms such asSARS, MERS and the novel coronavirus causing the current outbreak can be lethal. Coronaviruses werediscovered in the 1960s. On 31 December 2019, the outbreak was traced to a novel strain of coronavirus,which was labelled as 2019-nCoV by the World Health Organization (WHO). Human to human transmissionof coronaviruses is primarily thought to occur among close contacts via respiratory droplets generatedby sneezing and coughing. Clinical laboratories performing routine haematology, urinalysis, and clinicalchemistry studies, and microbiology laboratories performing diagnostic tests on serum, blood, or urine.There is currently no vaccine to prevent 2019-nCoV infection. The best way to prevent infection is to avoidbeing exposed to this virus.